A mountain not too high to climb: a qualitative study exploring facilitators and barriers to smoking cessation in a regional mental health service. (2nd January 2016) - McAllister, Margaret; Halliday, Lynne; Jobson, Heather; Jacobs, Terry; Flynn, Trudi; Kargillis, Christina; Oprescu, Florin; Lowe, John B
Abstract : Tobacco smoking is the largest single preventable cause of death and disease in Australia. Reports suggest that up to 88% of people who have mental health problems of any kind continue to smoke, even when in acute mental health units. Some organisations have adopted smoking-free policies; however, implementation of smoking cessation programmes in acute mental health units has had varied levels of success. This qualitative study examined the second attempt to implement a smoke-free policy in an acute mental health service in Queensland, Australia, to explore the facilitators and barriers to change. Post-process interviews conducted with 10 clinicians and consumers revealed facilitators and barriers within themes of Culture, Wellbeing and Strategy. Key barriers included a negative institutional culture, fear and inconsistent application of the policy (associated with staff attrition, workloads, policy loopholes and resistance). Key facilitators were positive leadership, adequate resources, staff and consumer engagement, supportive formal policy and staff unity. Analysis also suggested benefits in cultivating a non-restrictive, healthy and respectful environment, and deploying a clear, consistent strategy that includes planning, preparation, implementation and maintenance phases.